Enhancing Diffusion Model with Auxiliary Information Mining-Exploration and Efficient Sampling Mechanism for Sequential Recommendation - Song, Te; Qi, Lianyong; Liu, Weiming; Wang, Fan; Xu, Xiaolong; Zhang, Xuyun; Beheshti, Amin; Zhou, Xiaokang; Dou, Wanchun (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Sequential recommendation aims to capture the temporal dependencies of items in a user’s historical interactions and make recommendations based on this. Previous generative methods addressed the issue of data not directly reflecting user preference uncertainty by modeling the distribution of latent item representations. Diffusion model (DM)-based methods have achieved significant success due to their high-quality generation and stable training. However, they lack satisfactory user sequence representations to guide the generation process, impacting recommendation performance. Moreover, these methods overlook the drawback of slow inference speed, severely limiting their practical value. To obtain effective generative guidance signals and accelerate the recommendation process, we propose DAE4Rec. In this approach, a Graph Auto-Encoder (GAE) is used to obtain interpretable item node representations, revealing global transitions of items that previous methods struggled to uncover. Then, we use it to construct a generative guidance signal with lower coupling and variance for the diffusion model. Additionally, by employing a non-Markov chain derived from the forward diffusion process, it is the first to implement a ’skip-step’ reverse process in diffusion model-based methods. And a creatively designed compensator is used to bridge the performance gap caused by ’skip-step’. Extensive experiments on three real-world datasets demonstrate that DAE4Rec outperforms other state-of-the-art generative sequential recommenders.